Dengue vector surveillance (Aedes albopictus) with ovitrap and attractants from imperata immersion (Imperata cylindrica) - M. Rasyid Ridha; Budi Hairani; Akhmad Rosanji; Abdullah Fadilly; Gusti Meliyanie (Intelektual Pustaka Media Utama, 2020)
Efforts to control the vector in reducing the population of Aedes albopictus can be done by using attractants with ovitrap. This study aims to determine the variation of Imperata cylindrica raeusch's immersion straw immersion dose on the number of eggs and hatchability of Aedes albopictus in the laboratory. Research type is a true experiment with a completely randomized design (CRD). The material used is Imperata cylindrica raeusch soaking with 5%, 10%, 15%, 20% concentration and aquadest as a control with 5 replications. The results showed that Imperata grass soaking was proven to be effective as an attractant in Aedes albopictus mosquitoes and was able to inhibit the number of eggs that hatch. Utilization of Imperata straw soaking can be used as an additive in the ovitrap in dengue vector surveillance.